Guidelines for designing of online courses in blended and distance modality using the Moodle platform - Vladimir Estévez Arias, Dr. C. Orosmán; Sánchez Cervantes, M. Sc. Mislene María; Bazán Fernández, M. Sc. Lisbeth Zayas (Transformación, 2021)
Objective: The paper aims at providing guidelines for designing online courses using the Moodle platform in the blended and distance educational modalities.  Methods: The authors rely on theoretical methods such as analytical-synthetic, inductivedeductive and the rise from the abstract to the concrete in documentary review, and in the examination of Moodle platform supported courses. Result: Based on the analysis and remodeling of documents ruling virtual courses design, a set of guidelines is devised for blended and distance modalities.Conclusion: The authors arrived at the conclusion that by making available information about virtual course design characteristics features in the blended and distance modality, teachers’ performance in the virtual environment will be favored. The guidelines offered do not hindir their creative capacity.
Keywords: Higher Education; virtual university; distance education; ICT; open learning